Intracranial Arteriovenous Malformations as a Possible Cause of Endocranial Bone Lesions and Associated Neurological Disorder. (4th September 2012) - Janovic, A.; Milovanovic, P.; Sopta, J.; Rakocevic, Z.; Filipovic, V.; Nenezic, D.; Djuric, M.
Abstract Endocranial bone lesions have attracted intensive scientific debate on their aetiology. In recent literature, the lesions were almost exclusively interpreted as of infectious origin. In this paper, we give new insight into the aetiology of endocranial lesions, distinguishing the lesions of vascular origin from those caused by tuberculosis or other conditions. The analysis is based on a rare case of a young female individual who displayed multiple endocranial lesions with 'serpens endocrania symmetrica' morphology. The lesions were associated with an uncommon branching pattern of the middle meningeal artery and marked side differences in teeth pathology. Postcranial skeleton showed signs of the left upper limb weakness. The macroscopic finding of the endocranial lesions along with the skeletal evidence of neurological damage, together with characteristic radiological and histological features, can lead to diagnosis of arteriovenous malformations. This study aims to improve understanding of the aetiology of endocranial bone lesions. Copyright © 2012 John Wiley & Sons, Ltd.